PERKEMBANGAN INDUSTRI TRANSPORTASI OJEK ONLINE DI ERA 5.0 DARI PT. GOJEK INDONESIA - Jumhadi Jumhadi; Ana Susi Mulyani (Bajang Institute, 2023)
Technological progress is developing rapidly. Update the concept to Society 5.0, where people live side by side with technology. In addition to the internet that is present in life, transportation is one of the most important needs in everyday life. Public transportation is an alternative that is used by the community when the road conditions are overcrowded. Following technological advances, transportation has developed rapidly, so a new idea has emerged, known as online motorcycle taxis. The purpose of this paper is to determine the development of the online motorcycle taxi transportation industry in Indonesia. The development of the online motorcycle taxi transportation industry was investigated using the literature review method by conducting library research by reading various journals and other publications related to the research topic. The results of the discussion of this study indicate that online motorcycle taxi transportation in Indonesia is quite controversial in conventional transportation circles. However, apart from that, online motorcycle taxi transportation is in great demand by the public as an alternative transportation that is practical and efficient, and has a positive influence on the economy and social conditions in Indonesia.